2018
DOI: 10.1007/s00425-018-2952-4
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of QTL–allele system conferring drought tolerance at seedling stage in a nested association mapping population of soybean [Glycine max (L.) Merr.] using a novel GWAS procedure

Abstract: RTM-GWAS identified 111 DT QTLs, 262 alleles with high proportion of QEI and genetic variation accounting for 88.55-95.92% PV in NAM, from which QTL-allele matrices were established and candidate genes annotated. Drought tolerance (DT) is one of the major challenges for world soybean production. A nested association mapping (NAM) population with 403 lines comprising two recombinant inbred line (RIL) populations: M8206 × TongShan and ZhengYang × M8206 was tested for DT using polyethylene-glycol (PEG) treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 46 publications
0
26
0
3
Order By: Relevance
“…Theoretically, correction for multiple tests is unnecessary in multi-locus GWAS because all the potential genes or loci for complex traits are fitted to a single linear model and their effects are estimated and tested simultaneously. For example, 0.05 was chosen as the P -value threshold in QTN detection of Khan et al (2018). Although relaxing the stringency of significance level in multi-locus GWAS can identify more hits, confidence in these hits will drop significantly.…”
Section: Multi-locus Genome-wide Association Studies For Complex Traitsmentioning
confidence: 99%
“…Theoretically, correction for multiple tests is unnecessary in multi-locus GWAS because all the potential genes or loci for complex traits are fitted to a single linear model and their effects are estimated and tested simultaneously. For example, 0.05 was chosen as the P -value threshold in QTN detection of Khan et al (2018). Although relaxing the stringency of significance level in multi-locus GWAS can identify more hits, confidence in these hits will drop significantly.…”
Section: Multi-locus Genome-wide Association Studies For Complex Traitsmentioning
confidence: 99%
“…The significance of total and residual variances of each trait in two F4 populations were estimated by the general linear model for univariate (GLM-Univariate) with one-way analysis of variance (ANOVA), respectively. The broad-sense heritability (ℎ 2 ) and GEI heritability (ℎ 2 ) for combined environments (i.e., WW and DS) were estimated as follows [30]: ℎ 2 = 2 /( 2 + 2 / + 2 /nr) (4) and ℎ 2 = ( 2 / )/( 2 + 2 / + 2 /nr) (5). Here, 2 was genotypic variance, 2 was environmental variance, 2 was error variance, 2 was GEI variance, n (n = 2) was the No.…”
Section: Statistical Analysis Of Phenotypic Datamentioning
confidence: 99%
“…In this method, tightly linked SNPs are grouped into SNP linkage disequilibrium blocks (SNPLDBs) to generate multiple haplotypes or alleles per block/locus to match the multiple-allele property of the natural population. Quite recently KHAN et al, (2018) used this novel procedure and identified 73 and 38 QTLs with 174 and 88 alleles contributed main effect 40.43 and 26.11% to phenotypic variance (PV) and QTLenvironment interaction (QEI) effect 24.64 and 10.35% to PV for relative root length and relative shoot length that served as drought tolerance indicators, respectively. However the best approach would therefore be to combine the two methods of QTL mapping (traditional linkage mapping and AM) to minimize each other's limitations with maximum accuracy and utilization of resources (MAHUKU et al 2016).…”
Section: Association Mapping (Am) and Genome Wide Association Studiesmentioning
confidence: 99%